Exogenous H2S reduces oxidative stress induced by lipid mixture in HepG2 cells through USP22/SIRT1 axis - Xiaomeng Cui; Chengjun Li; Shuixiang He; Yarui Li (Scientific Reports)
Abstract H2S signal transduction involves various physiological processes, including promoting vasodilation, regulating lipid metabolism, inducing angiogenesis, improving oxidative stress and inflammatory response, and avoiding cell apoptosis. Oxidative stress is an important mechanism that causes the pathological progression of NAFLD. However, the effect and specific mechanism of exogenous H2S on oxidative stress in NAFLD are still unclear. Here, we investigated the specific regulatory mechanism of exogenous H2S on oxidative stress and inflammation induced by LM in HepG2 cells. HepG2 cells were stimulated with LM with or without GYY4137 (200 µM) treatment for 24 h. The levels of MDA, SOD, ROS, TNF-α, IL-6, and antioxidant related proteins of cells were detected. We found exogenous H2S remarkably reduced the levels of MDA, ROS, TNF-α and IL-6 and elevated SOD contents as well as the expression of antioxidant-related proteins in LM-induced HepG2 cells. Moreover, exogenous H2S improved the expression of USP22 protein in LM-induced HepG2 cells and inhibited the ubiquitination degradation of SIRT1 through USP22. After USP22 was knocked down, the efficacy of exogenous H2S on mitigating LM-induced oxidative damage and inflammatory reaction in HepG2 cells had been weakened. In conclusion, exogenous H2S inhibited SIRT1 ubiquitination degradation through USP22, thereby alleviating LM-induced oxidative stress and inflammatory responses in HepG2 cells.